The adoption and concerns of e-finance in Malaysia - Narayanasamy, Kogilah; Rasiah, Devinaga; Tan, Teck Ming (Springer US, 2011)
Technological advancement has brought a whole new way of delivering financial services around the world. E-finance industry in Malaysia has grown rapidly with the help of internet and conducting financial services are far easier now if compared to last time. Internet provided a new medium or channel in delivering financial services. However, there are also risks and challenges when using electronic finance. A total of 100 respondents had been targeted in completing this study. Survey method was utilized in collecting respondent's opinion and perception to test the variables. The target was companies which used electronic finance in delivering their services. Interviews were also conducted and relevant tests conducted which provided evidence to support the hypotheses for this study. It was found that e-finance was affected by security, revenue and cost dimensions, and technology architecture with the adoption of global technology.